2020
DOI: 10.1002/cbin.11502
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of circRNA_0007059 in the regulation of postmenopausal osteoporosis by promoting the microRNA‐378/BMP‐2 axis

Abstract: Increasing evidence suggests that postmenopausal osteoporosis (PMO), a severe disturbance, imposes heavy physical, psychosocial, and financial burdens and dramatically influences the quality of life of postmenopausal women. Circular RNAs (circRNAs) and microRNAs (miRs) play important roles in the occurrence and development of PMO. However, the roles of circRNAs and miRs in osteoporosis regulation still need to be further investigated. circRNAs with different expression levels in patients with PMO were screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…39 Previous studies have found that miR-93-5p and miR-378 were involved in the regulation of OP by binding to BMP-2, a number of active bone morphogenetic proteins. 46,47 Therefore, BMP-2 may play a critical role in miRNA-mediated regulation of OP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Previous studies have found that miR-93-5p and miR-378 were involved in the regulation of OP by binding to BMP-2, a number of active bone morphogenetic proteins. 46,47 Therefore, BMP-2 may play a critical role in miRNA-mediated regulation of OP.…”
Section: Discussionmentioning
confidence: 99%
“… 39 Previous studies have found that miR-93-5p and miR-378 were involved in the regulation of OP by binding to BMP-2, a number of active bone morphogenetic proteins. 46 , 47 Therefore, BMP-2 may play a critical role in miRNA-mediated regulation of OP. In our future study, we will further investigate whether microRNA-151a-3p functions in OP by directly binding to BMP-2.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that during osteoclast differentiation, the level of circRNA_009934 was also increased, and circRNA_009934 functioned as a ceRNA of miR-5107 to promote osteoclastogenesis [ 102 ]. Conversely, the overexpression of circ_0007059 reduced hBMSC differentiation into osteoclasts and bone morphogenetic protein 2 (BMP-2) in vitro by directly targeting miR-378 [ 103 ]. Liu et al have demonstrated that circHmbox1 could also suppress RANKL-induced osteoclasts differentiation by binding to miR-1247-5p [ 104 ].…”
Section: The Role Of Molecules In Osteoclast Regulationmentioning
confidence: 99%
“…Large numbers of circRNAs have been shown to play crucial roles in osteoporosis. For example, by studying 40 women with PMO (postmenopausal osteoporosis), Liu et al discovered that circZNF720 (circbase ID: circ_0007059) could attenuate osteoclast differentiation through the microRNA-378/BMP2 axis, which in turn repressed osteoporosis [ 22 ]. circPRIM2 (circbase ID: hsa_circ_0076906) binds to miR-1305 to regulate the expression of OGN (osteoglycin) and alleviate osteoporosis [ 23 ].…”
Section: Biogenesis and Characteristic Of Circrnasmentioning
confidence: 99%
“…Among 40 women with PMO (postmenopausal osteoporosis) and paired normal controls, Liu et al selected five samples for RNA sequencing, which showed that 250 differentially expressed circRNAs were present in osteoporosis, 64 circRNAs showed a decreasing expression trend, and 186 other circRNAs were increased (filtration criteria: |fold alternation | > 2 and P < 0.01). Among the six top circRNAs with different expression levels (circ_0043813, circ_0001649, and circ_0005654 were upregulated, circ_0007059, circ_0001204, and circ_0001795 were downregulated), Liu et al chose to examine circ_0007059 in osteoporotic samples and discovered that circ_0007059 expression was reduced in osteoporotic samples [ 22 ].…”
Section: Aberrant Expression Of Circrnas In Osteoporosismentioning
confidence: 99%